Habilidades de comunicación y su importancia en las actividades laborales de las secretarias ejecutivas de la movilizadora de frutas tropicales de producción y comercialización La Clementina – FRU.COM.CLE - Contreras Olea, Mary Carmen (2022)
The main theme of this research is: Communication skills and their importance in the work activities of the Executive Secretaries of the Tropical Fruit Mobilizer of Production and Commercialization The Clementina – FRU.COM.CLE. The following main objective has been set, which is: To determine the communication skills and their importance in the work activities of the Executive Secretaries. During the development of this work the research modality was implemented: Documentary, and Field, and in turn the type of research: Descriptive, which allowed to collect information on the variables of study. In addition, this research required the application of the Inductive and Deductive methods, from which information was obtained in a general and particular way, and which also allowed the development of solutions and conclusions on the problems posed. The use of the survey was of great importance to achieve the collection of information and subsequently to obtain the facts or problems that arise in the company, where it was detected the lack of knowledge and little importance that the secretaries have regarding the management of communication skills, especially when they are carrying out their work activities that may present difficulties in dealing with customers, bosses, co-workers, not having the capacity to resolve labor disputes, among others, this some of the results that could be known during this investigative process, and which should be taken into consideration when implementing training or strategies that allow the potential or generate knowledge on the main themes and other related topics. Keywords: communication skills, work activities, competences.